The Scientist Citizen and the Citizen Scientist: Blurring the Lines. (30th December 2019) - Warmbrod, Lane; Trotochaud, Marc; Connell, Nancy
Abstract: The scientific enterprise satisfies the innate human urge to understand the world; these efforts have led to both improvements and dangers to society. The storied history of relationships between scientists and citizens suggests that the lines between these 2 sectors of society are often blurred. Here we discuss these relationships on the context of animal welfare. We briefly outline the history of animal welfare in research, and the entry of citizens into the discussion, leading to the Animal Welfare Act of 1966. The commitment of scientists to society, in this context, is the act of whistleblowing in research. As medical and life sciences technologies continue to expand at breathtaking rates, the landscape that both scientists and citizens must navigate increases in complexity. We discuss the responsibility of both the scientist and the citizen, as members of the voting public, in the face of the challenges of the future.